Literature Review: The Role of Talent Management, Compensation Management, Job crafting, and Job Analysis on Private School Teacher Retention (International Forum of Researchers and Lecturers, 2024)
The purpose of this study is to examine how talent management, compensation management, job crafting, and job analysis in private schools influence teacher retention rates. This research employs a literature review methodology, gathering findings from scholarly publications and online resources such as Scopus, Google Scholar, ScienceDirect, ResearchGate, and GARUDA (Garda Rujukan Digital). According to the literature review, talent management may serve as a significant strategic approach for private schools, considering contextual factors such as comprehensive planning, selection and recruitment, training and development, and standardized compensation/salary. Compensation management aims to enhance teacher motivation in private schools by implementing fair practices for managing salaries, allowances, and incentives. Job crafting enables teachers in private schools to increase their engagement by tailoring their responsibilities to align with their interests and expertise. Furthermore, private school instructors can utilize job analysis as a critical analytical process by evaluating job tasks, defining task descriptions, analyzing outcomes, and setting clear targets.